Sustainable Development Policies: Implementation or Discourse - Tongdaeng, Wannapa (Journal of Social Development and Management Strategy, 2019)
The concept of “Sustainable Development” has focused on three interrelatedelements consisting of economic, social, and environmental development. Based on this concept, the objective of this study is to review the published international literature by five articles; although they have shown different perspectives of three emphasized elements, each one is a part of the paradigm of “Sustainable Development”. Moreover, the purpose of this study is to criticize and summarize main points, and to make suggestions for sustainable policy implementation, efficiently and effectively, in order to achieve eventually sustainable development goals.